SARS-CoV-2 Antibody Responses in Newly Recovered Patients from Covid-19 Infection - A Lateef, Imad; K Attallah, Younus; G Khalil, Khalil; A Ahmad, Arshed (Diyala Journal of Medicine, 2023)
Background: The coronavirus disease 2019 pandemic continues, causing considerable morbidity and mortality worldwide. Real-time reverse transcription polymerase chain reaction (RT-PCR) diagnostic assays are a goal standard for case ascertainment and diagnosis. Comparing to PCR, serological testing is advantageous with faster turn-around time, high-throughput and less workload. However, the clinical value of antibodies largely depends on the understanding of host antibody responses during infection. Immunoglobulin G (IgG)) in response to SARS-CoV-2 in patients newly recovered from different severity Covid-19 infection in Baquba-Iraq. Patients and Methods: In this cross sectional study a (93) patients with recent covid-19 infection who came to the central blood bank of Diyala for convalescent plasma donation for the period from the 1st June 2020 till 1st August 2020 were enrolled. The questionnaire form were filled regarding the time of infection, clinical manifestations, severity and polymerase chain reaction (PCR) results. While blood were taken for antibody titer measurement using the SARS-CoV-2 IgM and IgG VIDAS test. Results: Male constitute about 91% of the study population. About 74% of the cases were below 40 years old. Fifty four of the patients had mild disease, 28% had moderate severity while the other 18% had severe type of the disease. fatigue and fever were the most common symptoms and seen in 87%,84% respectively. IgM Antibodies start to be positive before 21 days post infection mainly in mild and moderate cases 100%, While 0% of severe cases were positive at this time. After 49 day from the time of the infection 67%and 75% of the mild and moderate cases where IgM positive respectively and 100% of the severe cases where IgM positive. IgG Antibodies were positive in 100%, 0% of the mild and severe cases respectively at 21 day post infection but it's positive in 100% of both mild and severe cases after 49 day post infection. Conclusion: : Although the serological response for SARS-CoV-2 appears in the first three weeks from the disease onset this response differs from patient to another according to the time from the infection and the severity of the infection.